(untitled) (Lundiana: International Journal of Biodiversity, 2006)
P. pilosum is recorded for the first time in Brazil. This is a species of chewing louse that participates as an invertebrate host in the biological cycle of a bird filarid. The possibility for this transmission to be occurring in Brazil is discussed and the reports about the participation of these parasites as bioagents spreaders are summarized.